Historical Profiling of Dry Eye Patients – Potential Trigger Factors and Comorbidities - Posa, Andreas; Sel, Saadettin; Dietz, Richard; Sander, Ralph; Paulsen, Friedrich; Bräuer, Lars; Hammer, Christian (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose Dry eye syndrome (DES) is one of the most common diseases of the ocular surface. Affected persons suffer from different subjective complaints, with sometimes severe impairment in the quality of life. The aetiology and pathogenesis are multifactorial, multifaceted, and not yet fully understood. The present study is intended to provide deeper insights into possible triggering factors and correlating comorbidities.Materials and Methods In German ophthalmological practices, 306 persons (174 women, 132 men, age: 18 – 87 years) were interviewed by questionnaire on concomitant diseases and possible further triggering factors. DES was diagnosed by an ophthalmologist in 170 cases. The statistical comparative analysis between persons with and without DES was carried out using the chi-squared test (SPSS statistical software).Results DES occurred with significantly (p < 0.05) increased frequency in women over 40 years of age, as well as in persons exposed to screen work, air conditioning, persons with chronic ocular inflammation, myomas (hysterectomy), dry skin, arterial hypertonicity in need of medication, cardiac arrhythmias, fatty liver, gastric ulcer, appendicitis, cholecystectomy, depression, hyperlipidaemia, hyperuricaemia, osteoporosis, and nephrolithiasis.Conclusion Some of the known comorbidities and DES risk factors, e.g., computer work or depression, were confirmed. In contrast, the higher prevalence of hyperlipidaemia, hyperuricaemia, osteoporosis, nephrolithiasis, and fibroids among DES patients has not previously been reported. Additional studies should be performed on causal connections between DES and specific comorbidities.
Keywords: dry eye; risk factors; influencing factors; concomitant diseases; cornea; conjunctiva